Teba and Cliff as the Commodification of Expanding Tourism in Ubud Bali - Pemayun, AA Gde Putra; Suidarma, I Made (International Research Journal of Management, IT & Social Sciences, 2017)
This study examines the "Teba and Cliffs as commoditization Expansion of Facilities in Ubud Bali Tourism" concept of tebe (the term of the Balinese to mention traditional land behind the house) where tebe is necessary and mandatory nature in accordance with one ejection is Asta Kosala Kosali. In an effort to supply the facility tebe land use is unavoidable, causing the land use tebe usually used for the preparation of traditional jobs in Ubud turned into the expansion of tourism facilities. Likewise, namely riverside cliff (cliff) high and steep (almost vertical hillside or steep-walled, high edge of the mainland as a separator of fields, next to the bottom.The modernization and globalization cause the world there are no boundaries between countries with other countries, both in the political, economic, cultural and information technology. Ubud traditional societies inevitably have to deal with the values of novelty in the global economic order and context of tourism. Contrasting traditional values, the commodification of the modernization and globalization of tourism in the context of a discourse that is counterproductive. Given each must be seen as complementary strengths does not mean there can not be harmony. Therefore, the introduction of new value to the culture deferential requires strategic action in interpreting and understanding the Balinese tradition in order to create a harmony of civilizations.Â